Effect of organic manure on growth and yield of dwarf late napiergrass on rocky marginal land - AHMAD WADI; FITRIANA AKHSAN; BASRI BASRI (Asian Journal of Agriculture, 2025)
Abstract. Wadi A, Akhsan F, Basri. 2025. Effect of organic manure on growth and yield of dwarf late napiergrass on rocky marginal land. Asian J Agric 9: 727-738. The use of organic manure is a sustainable strategy to improve forage production on low-fertility soils. This study evaluated the effect of different manure application levels on the growth and yield of Dwarf Late napiergrass (DL Napiergrass) cultivated on marginal land under a cut-and-carry system. The field experiment was conducted over two years in Galung Village, Barru District, South Sulawesi, Indonesia, using a randomized block design with four manure treatments: control (0.00), low (1.38), medium (2.88), and high (4.67 g N m-² per application), replicated three times. Manure was applied five times annually, and growth parameters, dry matter yield, nutrient content, and soil characteristics were measured. Data were analyzed using ANOVA and Duncan's Multiple Range Test (DMRT), while regression analysis assessed the relationship between Leaf Area Index (LAI) and Crop Growth Rate (CGR). Results showed that manure application significantly (P<0.05) enhanced plant height, tiller number, dry matter yield, and nutrient uptake compared with the control. The highest biomass production was obtained with high-level manure, yielding 33.98 tons/ha/year in the first year and 21.84 tons/ha/year in the second. Soil pH, nitrogen, and phosphorus also improved under manure treatments. LAI and CGR were strongly correlated, while the leaf blade-to-stem ratio remained unchanged. In conclusion, applying 4.67 g N m-² of organic manure per cycle is recommended to optimize DL Napiergrass productivity and soil fertility on marginal land, contributing to sustainable livestock feed production.